แนวความคิดเรื่องโลกในปรัชญาอินเดียสายอาสติกะ - อุดร รัตนภักดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1979)
The purpose of this research is to study the concept of the world in orthodox Indian Philosophy and to investigate the relationship between this concept with the others. With regard to the existence of the world, attempts will also be made to find out as to how different systems of orthodox Indian thoughts have proved it. The result of this research has exposed the fact that all orthodox systems of Indian thought consider the world to be objectively real; it is created and destroyed occasionally. Again it has revealed that the concept of the world is a fundamental one which connect to the others, because each system refers to this concept in its metaphysics in its in relation to the other e.g. Brahman or Ataman, jiva, and God, etc. Therefore in studying the problem of the world all other related problems are automatically studied. According to this research, we may conclude that the concept of the world in orthodox Indian philosophy can be divided into three groups. The first group consisting of Nyaya, Vaisesika and Mimamsa explains the world in term of pluralistic realism. The second group, viz Sankhya and Yoga, holds to the view of realistic dualism. The third, i.e. Vedanta, is divided into two eings, namely, the Advaita and the Visistadvaita. While the Advaita Vedanta’s view is theistic monism, the Visistadvaita Vedanta advocates the view of pantheistic realism. Although each system has some different points of view, all of them excepting Mimamsa believe that world is occasionally created and destroyed, that the world is objectively real even though it is not absolutely real to some systems, and the existence of the external world is sensibly provable. The suggestion for further research may be given here in some aspects, e.g. , to study the bondage and liberation in orthodox Indian philosophy in order to investigate the relationship between these concepts and the world. Finally we can understand the six philosophical systems of Indian thoroughly if we clearly understand these.